PEMANTAUAN KUALITAS UDARA DI WILAYAH SEKITAR SEMBURAN LUMPUR SIDOARJO - Wahjono, Heru Dwi (BPPT)
Air quality changes due to the discharge gas in the vicinity of the location of bursts of mud in Sidoarjo disrupt the activities of people who live around. Concerns of the dangers caused by gas can increase the burden of the problems already experienced by them. Surveys measuring several parameters of gas in the villages around bursts mud needs to be done to provide clear information about the condition of air quality ambien. The measurement data processing and analysis results are expected to be used as an input when the decision is necessary to avoid another disaster due to the gas leak in that area.Keywords : Air Polution, Sidoarjo mudflow, Gas Consentration Monitoring, Bubble gas